Prevalence of Organizational Cynicism Among Early Career Psychiatrists in Lithuania: An Exploratory Study - Ambrasas Laurynas; Vveinhardt Jolita (Organizacijų Vadyba: Sisteminiai Tyrimai)
This exploratory study aims to identify the prevalence of organizational cynicism among early career psychiatrists in Lithuania. In order to achieve the purpose, the following research questions were raised: What is the prevalence of organizational cynicism among early career psychiatrists in Lithuania and how does organizational cynicism differ depending on the sociodemographic characteristics of these specialists? All early career psychiatrists employed in Lithuanian health care institutions were invited to participate in the study, and 56 of them filled out questionnaires. The obtained data were processed using descriptive statistical methods. Significant differences in indicators of organizational cynicism were identified depending on the respondents’ place of study. In addition, organizational cynicism varied by specialty: psychiatry residents had the highest mean scores; while child and adolescent psychiatrists, had the lowest. The study provides valuable insights into understanding the nature of organisational cynicism in terms of dispositional, cognitive, affective and behavioural cynicism. The obtained findings may contribute to the development of further research by promoting targeted interventions to address cynical attitudes towards work among early career psychiatrists.